A PROPOSED MATHEMATICAL MODEL FOR THE VELOCITY PROFILE INTERNALLY TO A CONICAL DIFFUSER - Barbosa, D. L. M.; Vaz, D. A. T. D. R.; Vaz, J. R. P.; Figueiredo, S. W. O.; da Silva, M. O.; Blanco, C. J. C.; Mesquita, A. L. A. (Revista de Engenharia Térmica, 2013)
The use of diffusers around of the horizontal-axis wind turbines have been widely studied, since the diffuser provides an improvement in the turbine power coefficient. These diffusers are often called Diffuser Augmented Wind Turbines (DAWT’s). The DAWT’s have the feature to make efficiency exceeding the Betz limit (maximum energy flow extracted = 59.26%), due to the increasing of the internal mass flow by influence of the diffuser presence. Thus, the present work proposed a mathematical model describing the behavior of the velocity profile internally to a diffuser according to the characteristics of flow and geometry of a conical diffuser. The model results were compared with experimental data and showed good agreement.